Influências locais e globais na performance de responsabilidade social das empresas multinacionais da indústria automobilística brasileira - Pereira, Marcello Monteiro (2012)
The purpose of this work is to measure the performance of subsidiaries of Corporate Social Responsability (CSR) and compare the results according to various CSR strategies adopted (global or local). To achieve the proposed goals and respond to the research problem, we used a quantitative research methodology, specifically a survey of executives of multinational companies in the sector. From the universe of 450 companies, suppliers of the automotive industry, 78 questionnaires were obtained. Due to the existence of multiple variables, we used the structural equation model to analyze the data. The results show that a global CSR strategy has positive influences on the performance of CSR, since the adoption of a local strategy shows no significant results due to lack of commitment to engagement with stakeholders.